2007
DOI: 10.1165/rcmb.2006-0394oc
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Binding of Airway Nuclear Extracts to Polymorphic β2-Adrenergic Receptor 5′ Sequence

Abstract: Like other intronless G protein-coupled receptor genes, the ␤ 2 -adrenergic receptor (␤ 2 AR) has minimal genetic space for population variability, and has attained such via multiple coding and noncoding polymorphisms. Yet most clinical studies use the two nonsynonymous polymorphisms of the coding region for association analysis despite low levels of linkage disequilibrium with some promoter and 5UTR polymorphisms. To assess the potential for allele-specific transcription factor binding to ␤ 2 AR 5-flanking se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Therefore, it is presumably in linkage disequilibrium with one or more SNPs that lie within the promoter region, or another cis-acting regulatory element affecting TF binding (Tao et al, 2006;Panebra et al, 2007;2010;Murani et al, 2013). Examples of these variations are given by SNPs used to analyze ASE of the beta-2 adrenergic receptor (ADRB2) gene in swine muscle (Muráni et al, 2009) and humans (Panebra et al, 2007), for which variation in allelic expression seems to be caused by multiple cis-regulatory polymorphisms in both species (Panebra et al, 2007;2010;Murani et al, 2013). However, in the present study, none of the TFBSs found for the KCNJ11 gene were consistent with any SNPs already described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is presumably in linkage disequilibrium with one or more SNPs that lie within the promoter region, or another cis-acting regulatory element affecting TF binding (Tao et al, 2006;Panebra et al, 2007;2010;Murani et al, 2013). Examples of these variations are given by SNPs used to analyze ASE of the beta-2 adrenergic receptor (ADRB2) gene in swine muscle (Muráni et al, 2009) and humans (Panebra et al, 2007), for which variation in allelic expression seems to be caused by multiple cis-regulatory polymorphisms in both species (Panebra et al, 2007;2010;Murani et al, 2013). However, in the present study, none of the TFBSs found for the KCNJ11 gene were consistent with any SNPs already described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidences show that non-synonymous SNPs could drive differences in the transcriptional activation, protein expression and cellular localization of the mutant protein and have a potential pathological effect [58,59]. For instance, Panebra et al 2007 demonstrated that non-synonymous SNPs showing varying levels of LD with ADRB2 5 0 UTR SNPs (far upstream position) have a negative effect in obstructive lung phenotypes through altered transcription factor binding [59].…”
Section: Discussionmentioning
confidence: 99%
“…The fourth condition was concomitant treatments with isoproterenol and the aforementioned agents of the asthma condition. Nuclear extracts were prepared by using reagents from the NE-PER extraction system (Pierce, Rockford, IL) as previously described (19). Briefly, attached cells were placed on ice, and the medium was aspirated and washed three times with cold PBS.…”
Section: Methodsmentioning
confidence: 99%